Submissive Behavior and Cyber Bullying: A Study on the Mediator Roles of Cyber Victimization and Moral Disengagement - Bahtiyar Eraslan-Çapan; Fuad Bakioğlu (Psychologica Belgica, 2020)
In order to prevent cyberbullying and cyber-victim behaviors that are very common among adolescents, it is important to investigate the factors that underlie these behaviors. The purpose of the present study was to examine the mediator roles of cyber victimization and moral disengagement in the relationship between submissive behavior and cyber bullying. The participants involved 370 Turkish adolescent (female: 47%; male, 53%). The age of participants ranged between 12 and 19 years (M = 15.92, SD = 1.87). Data were collected using the Submissive Behavior Scale, the Cyber Bullying Scale, the Cyber Victimization Scale, and the Moral Disengagement Scale. The data were analyzed using structural equation modeling. A bootstrapping analysis was conducted in order to determine any indirect effects. Structural equation modeling results provided evidence of indirect effects of submissive behavior on cyber bullying mediated by cyber victimization and moral disengagement. Bootstrapping showed that submissive behavior exerted a significant indirect effect on cyber bullying via cyber victimization and moral disengagement. The findings emphasized the role of youth cyber victimization and moral disengagement in explaining the relationship between submissive behavior and cyber bullying. The results of the study were discussed based on relevant literature, and suggestions for future studies were made.